The Influence of the Problem-Based Learning Model on Students' Critical Thinking Ability in Mechanical Wave Material - Saadila Hayati; Gunawan Gunawan; Hikmawati Hikmawati (Balai Publikasi Indonesia, 2024)
The learning process is still teacher-centered, resulting in students being less active during learning. This research aims to increase the influence of the Problem-Based Learning model on students' critical thinking abilities in mechanical wave material. This quasi-experimental research uses a non-equivalent control group design. The research population included all students in class XI MIPA at one of the State High Schools in East Praya. Sampling used a purposive sampling technique so that 2 groups were obtained, namely 30 experimental class students and 30 control class students. The experimental class was given treatment in the form of using the Problem-Based Learning model, while the control class used the conventional model. Students' critical thinking abilities are obtained from the description questions they work on. Data from the pretest results of experimental class students obtained an average score of 25 and control class students obtained an average score of 23. The posttest scores showed that the critical thinking abilities of experimental class students were in the good category with an average score of 78.6 and the students in the control class were in the good category with an average score of 74.3. The research hypothesis was tested using the polled variance t-test at a significance level of 5%. Data analysis shows that the tcount value, namely 3.384, is greater than ttable, namely 2.002, which means that H0 is rejected and Ha is accepted, so it can be concluded that there is an influence of the Problem-Based Learning model on students' critical thinking abilities in mechanical wave material.